Unintended consequences - Woods, Stuart (Woods, Stuart. Stone Barrington novel., 2013)
Traveling to Europe under strange circumstances, attorney Stone Barrington finds himself at the center of an unusually complex mystery involving two unexpected invitations and an intricate puzzle that leads him into the rarified world of European billionaires.